How to define: a tutorial - Hansson, Sven Ove (Princípios: Revista de Filosofia (UFRN), 2010)
Practical methods are introduced for the construction of definitions, both for philosophical purposes and for uses in other disciplines. The structural and contentual requirements on definitions are clarified. It is emphasized that the development of a definition should begin with careful choice of a primary definiendum, followed by the selection of appropriate variables for the definition. Two methods are proposed for the construction of the definiens, the case list method and the method of successive improvements. Four classes of concepts are discussed that are particularly difficult to define: vague concepts, value-laden concepts, controversial concepts, and inconsistent concepts.